2022
DOI: 10.1080/13814788.2021.2003775
|View full text |Cite
|
Sign up to set email alerts
|

Adapting patients' oncological treatment through remote participation of general practitioners in multi-disciplinary consultation meetings: A feasibility study

Abstract: Background The general practitioner (GP) is central to managing patients with cancer, whose numbers are increasing worldwide. The GP’s involvement requires better coordination between involved partners, in particular oncologists and GPs. Objectives To conduct a feasibility study of remote participation of GPs in multi-disciplinary consultation meetings (MCMs). We analysed participation, participants’ satisfaction, and their impact on therapeutic decisions. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2
1

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(6 citation statements)
references
References 29 publications
0
6
0
Order By: Relevance
“…[...] It would certainly be good for the patient if we both say the same thing, right?" [ GP 5,32] "And then it's also good to grab the phone and say [to the oncologist]: let's talk brie y and honestly. [...] This is sometimes also this challenging borderline area, so that we should relate to each other trustfully, that we both mean it well."…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…[...] It would certainly be good for the patient if we both say the same thing, right?" [ GP 5,32] "And then it's also good to grab the phone and say [to the oncologist]: let's talk brie y and honestly. [...] This is sometimes also this challenging borderline area, so that we should relate to each other trustfully, that we both mean it well."…”
Section: Resultsmentioning
confidence: 99%
“…To improve interdisciplinary collaboration, studies implementing new strategies have shown some success: e.g. remote participation of GPs in multidisciplinary meetings at the cancer center or integrating GPs with speci c oncological skills in the center before the home return of patients [32,33]. Still, review of the literature shows that the direct oral communication during the active phase of cancer treatment should be further developed [34].…”
Section: Discussionmentioning
confidence: 99%
“…It's so complex, the third antibody or the third checkpoint-inhibitor for lung cancer, I don't know it." [ GP 10,33] Because of the knowledge gap it is di cult for GPs to determine the risk-bene t ratio or to estimate the end of a cancer treatment. The rapid changes in oncological treatment options may even lead to avoidance of talking about prognosis and EOL at all and the risk of supporting unrealistic expectations.…”
Section: ) Timing and Conduction Of Eol-conversationsmentioning
confidence: 99%
“…Normally I follow the hospital's recommendations." [GP 3,33] On the other hand, some situations seem problematic when opinions about treatment goals differ. Some GPs choose patient-empowerment as a strategy.…”
Section: "In Most Conversations I Leave It [The Prognosismentioning
confidence: 99%
“…Implementation methods are diverse: standardized mailing, use of electronic support and relational exchanges between health professionals. The timing of information exchange between health professionals can also vary: during the initial oncology consultation, during the multidisciplinary consultation [12], during the announcement of the diagnosis of cancer [13], for shared decision-making of cancer treatment decisions [6], or at the time of discharge from hospital [14]. The quality of information transmission impacts the quality of care, the satisfaction of patients and GPs, and results in more frequent use of primary care, and a decrease in the number of hospitalizations due to adverse effects of anti-neoplastic treatments [15].…”
Section: Introductionmentioning
confidence: 99%